2019
DOI: 10.3892/ol.2019.10988
|View full text |Cite
|
Sign up to set email alerts
|

High gene expression levels of VEGFA and CXCL8 in the peritumoral brain zone are associated with the recurrence of glioblastoma: A bioinformatics analysis

Abstract: The present study aimed to identify differentially regulated genes between the peritumoral brain zone (PBZ) and tumor core (TC) of glioblastoma (GBM), to elucidate the underlying molecular mechanisms and provide a target for the treatment of tumors. The GSE13276 and GSE116520 datasets were downloaded from the Gene Expression Omnibus (GEO) database. Differentially expressed genes (DEGs) for the PBZ and TC were obtained using the GEO2R tool. The bioinformatics and evolutionary genomics online tool Venn was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 50 publications
(62 reference statements)
0
19
0
Order By: Relevance
“…The GO terms were comprised of 3 parts: cellular component (CC), biological process (BP), and molecular function (MF). [ 31 ] DEGs of BP were involved in neutrophil activation, neutrophil mediated immunity, response to molecule of bacterial origin, lipopolysaccharide, positive regulation of cytokine production, and cell activation. CC analysis revealed that DEGs were markedly enriched tertiary granule, secretory granule membrane, tertiary granule lumen, and cytoplasmic vesicle lumen.…”
Section: Resultsmentioning
confidence: 99%
“…The GO terms were comprised of 3 parts: cellular component (CC), biological process (BP), and molecular function (MF). [ 31 ] DEGs of BP were involved in neutrophil activation, neutrophil mediated immunity, response to molecule of bacterial origin, lipopolysaccharide, positive regulation of cytokine production, and cell activation. CC analysis revealed that DEGs were markedly enriched tertiary granule, secretory granule membrane, tertiary granule lumen, and cytoplasmic vesicle lumen.…”
Section: Resultsmentioning
confidence: 99%
“…Temozolomide- resistant GBM shows high expression of TNFRSF12A and greater migratory capacity [ 29 ]. CXCL8/IL8 is a multifunctional cytokine which enhances the vascular permeability in GBM [ 30 , 31 ]; high expression of both VEGFA and CXCL8 can reduce the overall survival rate of GBM patients [ 32 ]. ADGRG1/GPR56 is a GPCR involved in adhesion signaling and HIF1A is a transcription factor, which has a critical role in GBM survival, resistance and invasion [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8, also known as chemokine (C-X-C motif) ligand 8,plays a very important role in tumor growth、invasion and metastases in an autocrine and paracrine maner [43] .Some researches demonstrated that CXCL8 was associated with many types of tumors,such as glioblastoma 、 lung ademocarcinoma、 hepatocellular carcinoma and colon cancer [44][45][46] . Luo et al [44] demonstrated that high gene expression levels of CXCL8 and VEGF was correlating with recurrent glioblastoma.Daniel et al [47] showed that IL-8 was strongly associated with glioma formation and progression mediated by activator protein-1(AP-1) and nuclear transcription factor-kappa(NF-кB) site.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL8, also known as chemokine (C-X-C motif) ligand 8,plays a very important role in tumor growth、invasion and metastases in an autocrine and paracrine maner [43] .Some researches demonstrated that CXCL8 was associated with many types of tumors,such as glioblastoma 、 lung ademocarcinoma、 hepatocellular carcinoma and colon cancer [44][45][46] . Luo et al [44] demonstrated that high gene expression levels of CXCL8 and VEGF was correlating with recurrent glioblastoma.Daniel et al [47] showed that IL-8 was strongly associated with glioma formation and progression mediated by activator protein-1(AP-1) and nuclear transcription factor-kappa(NF-кB) site. Liu et al [45] showed that CXCL8 was an independent unfavorable factor with recurrence free survival and overall survival in patients suffering from adenocarcinoma,and the human Dachshund homologue 1(DACH1) was able to antagonize CXCL8 through AP-1and NF-кB.Shen et al [46] reported that CXCL8 may induce tumor proliferation、invasiveness through induction of epithelial-mesenchymal transition via the phosphatidylinositol 3-kinase (PI3K)/protein kinase B(AKT)/nuclear factor-кB(NF-кB) pathway.Researches demonstrated that human meningioma cells secreted specifically the CXC chemokine-8 [48,49] .In our study,the differential expression of CXCL8 between two datasets suggested it as a important target.…”
Section: Discussionmentioning
confidence: 99%